Comparison of the Photodegradation of Imazethapyr in Aqueous Solution, on Epicuticular Waxes, and on Intact Corn (Zea Mays) and Soybean (Glycine Max) Leaves. Issue 2 (1st February 2019) - Anderson, Scott C.; Chu, Linh; Bouma, Chandra; Beukelman, Logan; McLouth, Rayna; Larson, Evan; Nienow, Amanda M.
Abstract: A direct, controlled comparison of the photodegradation of imazethapyr has been made between imazethapyr in aqueous solutions, imazethapyr on the surface of epicuticular waxes of corn and soybean plants, and imazethapyr on the surface of intact corn and soybean plant leaves. In some experiments, the imazethapyr solutions were allowed to evaporate partially or fully after application to better model environmental conditions. The photodegradation of imazethapyr was fastest in aqueous solutions ( k  = 0.16 ± 0.02 h −1 ) and slowest on the surface of corn and soybean plants ( k corn  = 0.00048 ± 0.001 h −1 and k soy  = 0.00054 ± 0.003 h −1 ). Experiments allowing evaporation during irradiation have intermediate rate constants (e.g., k corn  = 0.082 ± 0.005 h −1 ). Finally, identification of photoproducts was also examined on epicuticular waxes of corn and soybean plants for the first time.